THE INFLUENCE OF ORGANIZATIONAL VALUE AND STRATEGIC ENVIRONMENT ON VALUE CHAIN, COMMUNITY TRUST, COMPETITIVE ADVANTAGE AND ORGANIZATIONAL PERFORMANCE IN COURSE AND TRAINING INSTITUTIONS (LKP) - Nuryadi (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2020)
Organization that optimal performance can be achieved with believe and applying values organization, since the value of organization provides direction and purpose for employees. Support environment strategy not less important to improve performance organization, because of the landscape strategy can be used to detect and identify strength and weakness of the organization. Institution course and training in east java needs measures strategic to increase performance organization and grabbed excellence compete based on value organization, strategic environmental public confidence and value chain. To achieve research purposes, a dissertation is using the 42 of LKP in east java as the population. A unit of analysis used are a company owner manager (coordinator) marketing, manager (coordinator) education and one teachers. Conclusion dissertation is: (1) the value organization not affect the value chain; (2) value organization impact on public trust excellence compete and performance organization; (3) environmental strategy influence the value chain, public trust, excellence compete and performance organization; (4) value chain influential significantly to excellence compete and performance organization; (5) public trust influential significantly to excellence compete and performance organization; (6) excellence compete influential significant on the performance organization.